Too optimistic about optimism the belief that optimism improves performance. [article]. - Tenney, Elizabeth R.; Logg, Jennifer M.; Moore, Don A.
A series of experiments investigated why people value optimism and whether they are right to do so. In Experiments 1A and 1B, participants prescribed more optimism for someone implementing decisions than for someone deliberating, indicating that people prescribe optimism selectively, when it can affect performance. Furthermore, participants believe optimism improved outcomes when a person?s actions had considerable rather than little, influence over the outcome (Experiment 2). Experiments 3 and 4 tested the accuracy of this belief; optimism improved persistence, but it did not improve performance as much as participants expected. Experiments 5A and 5B found that participants overestimated the relationship between optimism and performance even when their focus was not on optimism exclusively. In summary, people prescribe optimism when they believe it has the opportunity to improve the chance of success-unfortunately, people may be overly optimistic about just how much optimism can do. - - (from the authors)
Keywords: Optimism-Periodicals.; Bias-Periodicals.; Accuracy-Periodicals.; Decision phase-Periodicals.; Performance-Periodicals.